Water Supply, Sanitation and Hygiene Situation in Nepal: A Review - Budhathoki, Chitra Bahadur (Journal of Health Promotion, 2019)
Federal Democratic Republic of Nepal is a landlocked country located in South Asia. Nepal has made its considerable efforts to improve the water supply and sanitation (WASH) situation in the country by formulating and enforcing a number of WASH policies, guidelines and acts for the last two decades. But WASH situation of Nepal has not been well documented so far. Aim of this article is to describe the situation of water supply, sanitation and hygiene (WASH) in Nepal by analyzing secondary data and information obtained from published and unpublished literature. About 97 of the total population have access to basics anitation facilities and 87 percent access to basic water supply facility. Sanitation coverage is95 percent in six Provinces and below 90 percent in Province no. 2 of Nepal. The momentum of sanitation coverage was accelerated immediately after internalization and implementation of the Sanitation and Hygiene Master Plan in 2011 and Nepal reaches at close to the elimination of open defecation. The gap between rich and poor in accessing to and using toilet facility has been narrowing down due to the nationwide sanitation campaigns. But there is disparity in accessing and using piped water between rich and poor. Only 25 percent of water supply systems are well functioning and 68 percent can supply water to water taps throughout year. One-fourth of the existing toilet facility across the country are poorly constructed that needs to be upgraded. The government should make consolidated and integrated efforts to reduce existing inequity in the WASH sector and enhance the sustainability of water supply and sanitation services.